2020
DOI: 10.1186/s13018-020-01673-y
|View full text |Cite
|
Sign up to set email alerts
|

An accelerometer-based navigation system provides acetabular cup orientation accuracy comparable to that of computed tomography-based navigation during total hip arthroplasty in the supine position

Abstract: Background: Inadequate acetabular component orientation is associated with postoperative impingement, dislocation, and accelerated polyethylene wear. Computed tomography (CT)-based navigation systems provide accuracy for total hip arthroplasty (THA) but are not available in all facilities. Accelerometer-based navigation systems are inexpensive, but their accuracy remains undetermined. This study compares the accuracy of cup orientation in THA using CT-based and accelerometer-based navigation systems. Methods: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…In recent years, simpler portable navigation systems have been developed, and their accuracy has been reported. The accuracy of cup placement by various portable navigation systems in the supine position is 2.6°-3.7° for RI and 2.8°-3.8° for RA [10][11][12]. Okamoto et al reported that in DAA-THA, the cup placement rate within ± 5° was 56.6% in the alignment guide group and 72.2% in the portable navigation (Hip Align ® ) group [13].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, simpler portable navigation systems have been developed, and their accuracy has been reported. The accuracy of cup placement by various portable navigation systems in the supine position is 2.6°-3.7° for RI and 2.8°-3.8° for RA [10][11][12]. Okamoto et al reported that in DAA-THA, the cup placement rate within ± 5° was 56.6% in the alignment guide group and 72.2% in the portable navigation (Hip Align ® ) group [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not assess radiographic inclination and version. Our photographic system calibrated by a custom accelerometer device is not validated, although accelerometer-based navigation systems have been validated in THA [ [30] , [31] , [32] ].…”
Section: Discussionmentioning
confidence: 99%
“…With image-free navigation systems, the inclination errors were reported to range from 2.9° to 3.7°, and the anteversion errors ranged from 4.2° to 6.8° [ 9 , 12 , 14 ]. With CT-based navigation systems, the absolute values of inclination errors were reported to range from 1.2° to 3.2°, and the anteversion errors ranged from 1.0° to 3.3° [ 12 , 15 – 19 ]. The results for navigation errors in the present study were comparable to those of previous studies of image-free navigation systems (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the dislocation rate of THA ranged from 0 to 8% with the conventional freehand technique [ 11 13 ], 0% with image-free navigation systems [ 12 14 ], and 0 to 0.5% with CT-based navigation systems [ 11 , 12 , 15 , 19 , 20 ]. Intraoperative navigation systems were shown to be useful for reducing the incidence of postoperative dislocation.…”
Section: Discussionmentioning
confidence: 99%